2018
DOI: 10.3389/fneur.2018.00292
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation as a Target for Intervention in Subarachnoid Hemorrhage

Abstract: Aneurysmal subarachnoid hemorrhage (SAH) is a sub-type of hemorrhagic stroke associated with the highest rates of mortality and long-term neurological disabilities. Despite the improvement in the management of SAH patients and the reduction in case fatality in the last decades, disability and mortality remain high in this population. Brain injury can occur immediately and in the first days after SAH. This early brain injury can be due to physical effects on the brain such as increased intracranial pressure, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
98
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 106 publications
0
98
0
6
Order By: Relevance
“…Increases in arterial blood pressure and intracranial pressure, and decreases in cerebral blood flow, cerebral perfusion pressure and oxygen tension are observed in EBI (2)(3)(4). Cerebral inflammation, oxidative stress and neuronal apoptosis are involved in the pathogenesis of EBI following SAH (1,2,5,6). Previous clinical studies reported that the 120, 145 and 150 kDa fragments of the 280 kDa neuronal cytoskeletal protein α-II spectrin are elevated in the cerebrospinal fluid of patients with SAH, and revealed that these fragments are potential biomarkers for the severity of aneurysmal SAH (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Increases in arterial blood pressure and intracranial pressure, and decreases in cerebral blood flow, cerebral perfusion pressure and oxygen tension are observed in EBI (2)(3)(4). Cerebral inflammation, oxidative stress and neuronal apoptosis are involved in the pathogenesis of EBI following SAH (1,2,5,6). Previous clinical studies reported that the 120, 145 and 150 kDa fragments of the 280 kDa neuronal cytoskeletal protein α-II spectrin are elevated in the cerebrospinal fluid of patients with SAH, and revealed that these fragments are potential biomarkers for the severity of aneurysmal SAH (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Patients who survive an early stage of aneurysmal SAH and have their aneurysms obliterated are still at risk of delayed cerebral ischemia (DCI) that often results in severe disabilities or death [1][2][3]. The mechanisms of post-SAH brain injury are multifactorial, but neuroinflammation is considered as an important cause [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Circulating HMGB1 can be released from various cells, including activated platelets [31,37]. The activation of platelets is a known phenomenon in SAH and is associated with early brain injury after SAH [3,38]. Thus, one can speculate that in the acute period after IA rupture, there is a tendency to decrease the production of HMGB1 in peripheral leukocytes; however, due to its release from other sources, including activated platelets, the plasma levels continue to rise.…”
Section: Discussionmentioning
confidence: 99%
“…The rupture of an intracranial aneurysm (IA) resulting in a subarachnoid hemorrhage (SAH) results in many systemic effects and strongly influences the functioning of the immune system. Alterations in inflammation-related protein levels in peripheral blood and in the number and activity of immune cells have been reported [1][2][3]. These changes are associated with the systemic consequences of IA rupture, including inflammatory responses and immunodepression, which might be critical for patient outcomes.…”
Section: Introductionmentioning
confidence: 99%